EXPLORING THE LANGUAGE LEARNING MATERIALS USED OUT-OF-CLASS BY MALAYSIAN TESL STUDENTS AND STUDENTS OF TBFL - Jayakaran Mukundan; Laleh Khojasteh; Nigel Pearson (Indonesian JELT, 2009)
This study recognizes that disconnection between language learning experiences inside and outside of the classroom may create negative feelings for learners. It posits that while learner attitude and motivation contribute to language acquisition, it also impacts on out-of-class language learning behavior. This study is significant in that it focuses on the materials learners use outside the classroom to support their use and development of target language ability. The objectives of the study were to uncover similarities and differences in the out-of-class language learning materials used by Malaysian TESL students and Malaysian students of Bahasa Malaysia. Following on from this, suggestions for improving language acquisition, out-of-class or classroom based were explored. Fifty UPM TESL students and 50 students of TBFL completed an out-of-class language learning survey. SPSS software was applied to carry out the statistical procedures needed to collate and analyze the data. A range of implications for educators and those involved in development of teaching materials is discussed.Keywords:   Language learning experiences; language acquisition; language learning behavior; language learning materials